Numerical study of the impact of filters located in the exhaust duct of a low-voltage circuit breaker - Rochette, David (2015)
Low-voltage circuit breakers under critical situa- tions such as a severe short circuit develop a strong electric arc leading to brutal manifestations such as envelope rupture or fire. Apparatus are strictly designed to avoid damages like personal injury and material destruction. To limit the external manifestations of the electric arc, an efficient way consists of inserting a porous filter in the gas exhaust duct, composed of metallic cloth arranged in a Reps structure. Experimental tests have demonstrated the efficiency of this technique. We propose to complete the experimental study by carrying out the numer- ical simulations about the filter impact on the hot gas flow. A 2-D model based on the gas flow in porous media is considered, taking into account the porosity variation while the electric arc model derives from the experimental data and a thermal radiation model. A sophisticated finite-volume method based on a well-balanced scheme developed for nonconservative system is used to correctly approximate the solution when dealing with porosity variation.